NON-ART OBJECTS ARE THE PHILOSOPHY OF SOPHISTICATION. AESTHETICS OF NATURE - Kadirova Dilbar Solihovna; Zarina Abduazimova Amirovna. (Scholar Express Journal, 2023)
In the article, the aesthetics of non-art objects, its place in the knowledge of the world and in human practice, the emergence of aesthetic activities related to nature, the preservation of natural beauties and the study of their influence on human aesthetic feelings, the connection of the understanding of the beauty of nature with the ideals and standards of the time, harmony in nature, historically the emergence of several networks combining nature and art, the landscape and the place of harmony, rhythm, fractals, artistic styles and their expression in landscape design are studied.
Keywords: Aesthetics of nature; aesthetic activity; shape; color